2014
DOI: 10.3807/josk.2014.18.6.706
|View full text |Cite
|
Sign up to set email alerts
|

Advanced 360-Degree Integral-Floating Display Using a Hidden Point Removal Operator and a Hexagonal Lens Array

Abstract: An enhanced 360-degree integral-floating three-dimensional display system using a hexagonal lens array and a hidden point removal operator is proposed. Only the visible points of the chosen three-dimensional point cloud model are detected by the hidden point removal operator for each rotating step of the anamorphic optics system, and elemental image arrays are generated for the detected visible points from the corresponding viewpoint. Each elemental image of the elemental image array is generated by a hexagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In addition, the data amount for a given field of view in curved hologram is smaller than a planar hologram [2]. Furthermore, cylindrical geometry has proved efficient in 3D volumetric imaging, such as computed tomography, magnetic resonance images, and integral-floating display [3]. However, the heavy computation load is one of the issues.…”
mentioning
confidence: 99%
“…In addition, the data amount for a given field of view in curved hologram is smaller than a planar hologram [2]. Furthermore, cylindrical geometry has proved efficient in 3D volumetric imaging, such as computed tomography, magnetic resonance images, and integral-floating display [3]. However, the heavy computation load is one of the issues.…”
mentioning
confidence: 99%
“…There are many research efforts implemented for this technique, such as the extension of the depth of field (DOF) [5,6] , the enlarging of the viewing angle [7][8][9] , the highly efficient computer-generated encryption image method [10] , and the improvement of resolution [11,12] . On the base of the above-mentioned studies, it can be concluded that II has the potential to realize the floating 3D effect [13] . According to the primary aberration theory, lens distortion seriously deteriorates the 3D image quality.…”
mentioning
confidence: 99%
“…Advanced glass lenses are important components to many modern technologies [1][2][3][4][5]. A lithography process in the semiconductor industry, for example, relies on the quality of its optical system [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%